DEMAND ANALYSIS OF MARINE FISH IN SOUTH CILACAP SUB-DISTRICT: A LINEAR APPROXIMATE ALMOST IDEAL DEMAND SYSTEM (LA AIDS) MODEL APPROACH - Salsabila, Diva Tasya; Sambodo, Herman; Suharno, Suharno (Jurnal AGRISEP, 2023)
This research aims to analyze the factors that influence the demand and its elasticity for marine fish in the South Cilacap Sub-District, Cilacap Regency. For data collection, interviews and questionnaires were used with respondents consisting of 100 households, while the Almost Ideal Demand System (AIDS) was used for analysis. According to the results, the demand for marine fish was influenced by several factors, namely price, fish expenditure, income, number of family members, and tastes. Also, the price of elasticity of the four fish commodities was inelastic. Income elasticity of tuna, skipjack, and squid were inferior goods, while shrimp were luxury goods. The cross-price elasticity of the four fish commodities is more complementary. This research suggests that the relevant government agencies must improve facilities and infrastructure to maintain the quality and availability of fresh marine fish commodities. The Government through related departments or managers of local Fish Auction Places (TPI) need to improve facilities and infrastructure as well as improve infrastructure, for example providing fish coolers so that quality is maintained and ensuring the availability of fresh marine fish commodities can be maintained. Furthermore, the gemarikan program (love eating fish program) can be maximized to increase the taste and awareness, and interest of the people of Cilacap Regency in consuming marine fish as a side dish.